Comprehensive Study of Personal Data Protection in Iran's Legal System and European General Data Protection Regulations - Fatemeh Ghanad; Elham Sharif (حقوق فناوریهای نوین, 2021)
Protecting the privacy of individuals has always been considered a global principle by international institutions and has been stipulated in many international documents. Nowadays, lawmakers have considered personal data more than ever due to the fast pace of the technology and consequently the availability of personal data in cyberspace, their ease of transfer, and the convenience of their processing. The EU has been a frontrunner and, as a comprehensive alternative to the EU Data Protection Act, set out the International Document of General Data Protection Regulations (GDPR) in April 2016, which was approved and implemented by the European Parliament on May 25, 2018. This article aims to demonstrate the scope of personal data and its protection in the General Data Protection Regulations as an international document and Iran's legal system. It further recommends some improvements in cyberspace infrastructures and regulations and the necessity of better designating regulatory bodies to protect individual privacy better